2020
DOI: 10.1186/s10194-020-01089-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sumatriptan and ketorolac trometamol in the human experimental model of headache

Abstract: Background: Pituitary adenylate cyclase-activating polypeptide-38 (PACAP38) induces headache in healthy volunteers but the precise mechanisms by which PACAP38 leads to headache are unclear. We investigated the headache preventive effect of sumatriptan and ketorolac on PACAP38-induced headache in healthy volunteers. In addition, we explored contribution of vascular mechanisms to PACAP38-induced headache using high resolution magnetic resonance angiography. Methods: Thirty-four healthy volunteers were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Sumatriptan has been administered in doses up to 96 micrograms/kg in experimental settings (Perrin et al 1989) with the most effective dose being 64 micrograms/kg (Perrin et al 1989), corresponding to 4.3 mg in a 67 kg person. This dose has recently been administered intravenously in healthy volunteers without any major side effects (Ghanizada et al 2020a). Sumatriptan has a bioavailability of approximately 96% with intravenous administration, and intravenous infusion of sumatriptan has previously resulted in pain relief within 10-30 minutes in patients with migraine (Perrin et al 1989) .…”
Section: Randomization and Maskingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumatriptan has been administered in doses up to 96 micrograms/kg in experimental settings (Perrin et al 1989) with the most effective dose being 64 micrograms/kg (Perrin et al 1989), corresponding to 4.3 mg in a 67 kg person. This dose has recently been administered intravenously in healthy volunteers without any major side effects (Ghanizada et al 2020a). Sumatriptan has a bioavailability of approximately 96% with intravenous administration, and intravenous infusion of sumatriptan has previously resulted in pain relief within 10-30 minutes in patients with migraine (Perrin et al 1989) .…”
Section: Randomization and Maskingmentioning
confidence: 99%
“…Every 10 mins patients were asked to remain still with closed eyes for at least 5s to obtain a scaled color-coded image with red color for high perfusion and blue color for low perfusion. The use of laser speckle contrast imaging to measure blood flow has previously been described (Briers 2001;Ghanizada et al 2020a).…”
Section: Flushing and Facial Edemamentioning
confidence: 99%
“…④ Ketorolac tromethamine can selectively aggregate the pain site, thus increasing the drug concentration, which makes the analgesic effect stronger, the action time longer, and the sedative effect stronger ( 21 ). ⑤ Some scholars have found that ketorolac tromethamine may have an effect on the hypothalamic prostate system In addition, its analgesic effect may be related to the synthesis and participation of nitric oxide ( 22 , 23 ). However, more experiments are needed to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…It should come as no surprise, therefore, that direct topical application of local anesthetics and sumatriptan have reduced both frequency and magnitude of headaches. 3,4 The principal neurotransmitter is glutamine.…”
Section: Painmentioning
confidence: 99%